2011
DOI: 10.1242/bio.2011014
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal spores host bacteria that affect nutrient biodynamics and biocontrol of soil-borne plant pathogens

Abstract: SummaryThe aim of this research was to isolate and characterize bacteria from spores of arbuscular mycorrhizal fungi (AMF). We designated these bacteria ‘probable endobacteria’ (PE). Three bacterial strains were isolated from approximately 500 spores of Gigaspora margarita (Becker and Hall) using a hypodermic needle (diameter, 200 μm). The bacteria were identified by morphological methods and on the basis of ribosomal gene sequences as Bacillus sp. (KTCIGM01), Bacillus thuringiensis (KTCIGM02), and Paenibacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 34 publications
2
55
0
2
Order By: Relevance
“…Since reports suggest that these microorganisms may influence the performance of plants (Cruz and Ishii 2011;Cruz et al 2008;Cameron et al 2013), the observed responses of heartsease in mycorrhizal treatments could be affected by these microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Since reports suggest that these microorganisms may influence the performance of plants (Cruz and Ishii 2011;Cruz et al 2008;Cameron et al 2013), the observed responses of heartsease in mycorrhizal treatments could be affected by these microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…rpoB primer has been used as a convenient tool to analyze the phylogenetic tool of many actinomycetes genera like Mycobacterium (Kim et al, 1999) and this primer is found to be more useful than 16S rRNA gene for identifying closely related species of actinomycetes (Kim et al, 2003). Cruz and Ishii (2011) reported the isolation of endobacteria from the arbuscular mycorrhizal fungi Gigaspora margarita by using hypodermic needle method and identified through the 16S rRNA analysis and found to have properties of phosphorus solubilization, ethylene production, nitrogenase activity (NA), and stimulation of AMF hyphal growth. They were also antagonistic to soil borne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…AM fungi promote plant growth, nutrient mobilization and also exhibit bio-control activity in the plant they colonize (Sousa et al, 2008;Bonfante and Anca, 2009). The beneficial traits exhibited by AM fungi are in synergism with some associated bacteria called mycorrhizal helper bacteria (MHB) (Cruz and Ishii, 2011) and these MHB play main role in growth and spore germination of the AM fungi and the absence of the MHB is highly affecting the ecological fitness of AM fungi (Lumini et al, 2007). Naumann et al (2010) through their studies describe a vertically inherited, monophyletic and globally distributed lineage of endobacteria thriving in arbuscular mycorrhizal cytoplasm also identified the association of bacteria Among the MHB, Actinomycetes sp (Gram positive aerobic Bacteria) have received much attention due to their growth promoting attributes and antagonistic activity against pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…These environmental factors could be climate, weather conditions, character of soil, composition of indigenous microbes in the soil and competition among natural microbes in the soil. Cruz and Ishii (2012) also stated that the activity of probable endobacteria (PE) isolated from spores of AMF Gigaspora margarita in vitro, may not reflect their activity in the soils, especially for the bacteria living on the surface of the spore.…”
Section: Discussionmentioning
confidence: 99%